A Digital Twin-Based Platform for Medical Cyber-Physical Systems - Messaoud Rahim; Wassila Lalouani; Elbahi Toubal; Lloyd Emokpae (IEEE Access)
A Medical Cyber-Physical System represents a sophisticated healthcare framework seamlessly integrating cyber and physical elements to enhance medical processes and diagnostics. The integration of Artificial Intelligence (AI) into the healthcare system has been pivotal in advancing intelligent medical cyber-physical systems and ushering in an era of advanced healthcare solutions. The paradigm of smart hospitals aspires to implement intelligent solutions seamlessly integrating hardware and software to control, supervise, and monitor patients while assisting healthcare professionals. Such solution is essential for smart decision-making and enhancing healthcare services. However, complete utilization of this intelligent medical cyber-physical system relies on an effective framework that should facilitate the interaction among patients, medical devices, AI services and hospital staff. This paper introduces a Digital Twin-based Smart Medical Cyber-Physical System (DT-MCPS) designed to enhance smart hospitals. Leveraging Digital Twins technology, DT-MCPS constructs a virtual replica of the hospital, facilitating precise control and supervision of patient care, coupled with service optimization through comprehensive data integration. DT-MCPS promotes personalized decision-making by seamlessly integrating medical records and real-time monitoring of physiological data, enabling predictive insights into disease progression. Moreover, DT-MCPS employs a model-based platform founded on web services to monitor the patient’s state in real-time while accurately simulating the hospital medical systems workflows and contributing to long-term health management. Experimental results showcase the efficacy of DT-MCPS in enhancing hospitalization services, streamlining real-time control, and achieving highly precise personalized patient diagnostic.